2015
DOI: 10.5751/es-07733-200333
|View full text |Cite
|
Sign up to set email alerts
|

Meanings, drivers, and motivations for community-based conservation in Latin America

Abstract: ABSTRACT. Indigenous and rural communities have developed strategies aimed at supporting their livelihoods and protecting biodiversity. Motivational factors underlying these local conservation strategies, however, are still a largely neglected topic. We aimed to enrich the conceptualization of community-based conservation by exploring trigger events and motivations that induce local people to be engaged in practical institutional arrangements for successful natural resource management and biodiversity conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 52 publications
0
48
0
1
Order By: Relevance
“…In externally driven monitoring schemes, motivation is often linked to incentives offered to the communities or to the individuals involved. These incentives may be the ability for local participants to use the collected data for decisionmaking and management (Constantino et al 2012;Boissière et al 2013), recognition of tenure rights (Veer et al 2006;Ruiz-Mallén et al 2015), recognition of legal access (Van Rijsoort and Jinfeng 2005;Funder et al 2013), and pecuniary benefits (Rode et al 2015;Ruiz-Mallén et al 2015). By contrast, autonomous monitoring can occur even if these benefits are not offered.…”
Section: Motivation To Engage In Forest Monitoringmentioning
confidence: 99%
“…In externally driven monitoring schemes, motivation is often linked to incentives offered to the communities or to the individuals involved. These incentives may be the ability for local participants to use the collected data for decisionmaking and management (Constantino et al 2012;Boissière et al 2013), recognition of tenure rights (Veer et al 2006;Ruiz-Mallén et al 2015), recognition of legal access (Van Rijsoort and Jinfeng 2005;Funder et al 2013), and pecuniary benefits (Rode et al 2015;Ruiz-Mallén et al 2015). By contrast, autonomous monitoring can occur even if these benefits are not offered.…”
Section: Motivation To Engage In Forest Monitoringmentioning
confidence: 99%
“…Other types of non-externally driven CBM strategies exist, including: (i) strategies aiming to devolve or recognize existing community rights and responsibilities based on concerns of environmental and social justice (Brosius et al 1998;Myers and Muhajir 2015); (ii) long-term CBM strategies based on customary practices that result in conservation (Ostrom 1990;Ruiz-Mallén et al 2015); and (iii) collective common pool resource management, often associated with co-management strategies (Hauzer et al 2013;Ruiz-Ballesteros and Gálvez-García 2014). Fewer studies have investigated these internally-driven initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…COMBIOSERVE found that the drivers and motivations for community-based conservation of indigenous communities in Brazil, Bolivia, and Mexico differed considerably as a result of distinct external and internal (intracommunity) processes that determine social-ecological change (Ruiz-Mallén et al 2015a). For example, in the Calakmul community in Mexico, a key driver of conservation is a statedriven policy for direct forest conservation through a payment for ecosystem services (PES) program, which involves a 5-year payment renewable and collective contract.…”
Section: Models Of Governancementioning
confidence: 99%
“…For example, the establishment of the Coroa Vermelha Indigenous Territory in 1997 allowed the Pataxó to gain formal usufruct rights over such territory lands, and they in turn set aside an area of 827 ha to preserve the forest against urbanization pressures. And while the arrival of tourists to the region and the need to gain further social recognition as an indigenous group helped consolidate the locally protected area over time, the increase in tourism represents a challenge for conservation if, over time, it contributes to displacing culturally rooted conservation principles without a balance between ethnotourism initiatives and sustainable, economically profitable resource management (Ruiz-Mallén et al 2015a). …”
Section: Models Of Governancementioning
confidence: 99%